PENGARUH BAURAN PEMASARAN TERHADAP PERILAKU ANGGOTA KOPERASI DALAM MEMAKAI PRODUK SIMPANAN (STUDI PADA KOPERASI JASA KEUANGAN SYARIAH BAITUL MAAL WA TANWIL AMANAH UMMAH KARTASURA SUKOHARJO) - Widayati, Nurul; Joyoatmojo, Soetarno; M.Bus, Susilaningsih (Jurnal Pendidikan Insan Mandiri, 2014)
The objective of this research are to knows: 1)  a simultaneously effect of the marketing mix on the behaviors of the members in utilizing the product of savings. 2) the effect of product on the behaviors of the members in utilizing the product of savings, 3) the effect of place partially on the behaviors of the members in utilizing the product of savings, 4) the effect of price partially on the behaviors of the members in utilizing the product of savings, 5) the effect of promotion  partially on the behaviors of the members in utilizing the product of savings, 6) the effect of people partially on the behaviors of the members in utilizing the product of savings, 7) the effect of process partially on the behaviors of the members in utilizing the product of savings, 8) the effect of physical evidence partially on the behaviors of the members in utilizing the product of savings.   This research used the descriptive quantitative one with the survey method. The population of the research was the members of KSKS BMT Amanah Ummah of Kartasura utilizing its product of savings. The samples of the research consisted of 80 respondents, and they were taken by using the accindental sampling technique. The data of the research were gathered through questionnaire. They were then analyzed by using multiple regression analysis, f-test, and t-test. Before the data were analyzed, the classical assumption pre-requisite tests, namely: multicolinearity test, heteroskedasticity test, and normality test had been conducted.                            The result of the research are: 1) there is a simultaneously effect of the marketing mix on the behaviors of the members in utilizing the product of savings (63,525>2,71), 2) product partially have a effect on the behaviors of the members in utilizing the product of savings (2,590<2,00), 3) place partially do not have a significant effect on the behaviors of the members in utilizing the product of savings (1,848<2,00), 4) price partially has effect on the behaviors of the members in utilizing the product of savings ( 2,702 >2,00), 5) promotion is partially has effect on the behaviors of the members in utilizing the product of savings (3,204>2,00), 6) people partially has effect on the behaviors of the members in utilizing the product of savings  (2,787>2,00), 7) process partially has effect on the behaviors of the members in utilizing the product of savings (2,227>2,00),  8)  physical evidence partially has effect on the behaviors of the members in utilizing the product of savings (1,147<2,00).Keywords:     Marketing mix, Syariah banking, the behaviors of the members, and KJKS BMT.